Hypophagia induced by salmon calcitonin, but not by amylin, is partially driven by malaise and is mediated by CGRP neurons - Lavinia Boccia; Tito Borner; Misgana Y. Ghidewon; Patricia Kulka; Chiara Piffaretti; Sarah A. Doebley; Bart C. De Jonghe; Harvey J. Grill; Thomas A. Lutz; Christelle Le Foll (Elsevier, 2022)
Objective: The behavioral mechanisms and the neuronal pathways mediated by amylin and its long-acting analog sCT (salmon calcitonin) are not fully understood and it is unclear to what extent sCT and amylin engage overlapping or distinct neuronal subpopulations to reduce food intake. We here hypothesize that amylin and sCT recruit different neuronal population to mediate their anorectic effects. Methods: Viral approaches were used to inhibit calcitonin gene-related peptide (CGRP) lateral parabrachial nucleus (LPBN) neurons and assess their role in amylin's and sCT's ability to decrease food intake in mice. In addition, to test the involvement of LPBN CGRP neuropeptidergic signaling in the mediation of amylin and sCT's effects, a LPBN site-specific knockdown was performed in rats. To deeper investigate whether the greater anorectic effect of sCT compared to amylin is due do the recruitment of additional neuronal pathways related to malaise multiple and distinct animal models tested whether amylin and sCT induce conditioned avoidance, nausea, emesis, and conditioned affective taste aversion. Results: Our results indicate that permanent or transient inhibition of CGRP neurons in LPBN blunts sCT-, but not amylin-induced anorexia and neuronal activation. Importantly, sCT but not amylin induces behaviors indicative of malaise including conditioned affective aversion, nausea, emesis, and conditioned avoidance; the latter mediated by CGRPLPBN neurons. Conclusions: Together, the present study highlights that although amylin and sCT comparably decrease food intake, sCT is distinctive from amylin in the activation of anorectic neuronal pathways associated with malaise.